Cover Picture: Influence of Metal Fragment Mobility and Solution Dynamics on Cationic Rearrangements in Multimetallic Alkoxide Frameworks (ChemistrySelect 01/2018). Issue 1 (2nd January 2018) - Hegemann, Corinna; Heidemann, Tim; Pantenburg, Ingo; Mathur, Sanjay
Abstract : The cover picture shows the rearrangement of alkoxide fragments in solution. This solution dynamics often hinder the controlled formation of trimetallic alkoxides. A step‐by‐step approach using alkoxide building blocks offers a convenient method to trimetallic alkoxides with a variable composition of included metals. Further details of the results can be found in the Full paper by Hegemann and Heidemann et al. (Design: Dr. Tim Heidemann) (DOI:10.1002/slct.201702252 )